2022
DOI: 10.1021/acs.macromol.2c00810
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of One-Handed Helical Polymers Carrying Achiral Organoiodine Pendants for Enantioselective Synthesis of Quaternary All-Carbon Stereogenic Centers

Abstract: Inspired by highly efficient and enantioselective reactions catalyzed by biomacromolecules, developing artificial helical polymer-based catalysts for enantioselective reactions is an interesting work. In this work, a series of one-handed helical polyisocyanides bearing aryl iodine pendants were readily produced via asymmetric polymerization of achiral isocyanides using chiral Pd(II)-catalysts. Despite the inexistence of any stereogenic centers, these polymers showed large optical activity owing to the one-hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…A mechanism for the helical polyisocyanide catalyzed asymmetric reactions was proposed (Fig. 5a) [62][63][64] . Taking the asymmetric Kita-Spirocyclization as an example, the phenyl iodine pendants of polyisocyanide were initially oxidized to active hypervalent iodane (IA) by mCPBA.…”
Section: Mechanism Studymentioning
confidence: 99%
“…A mechanism for the helical polyisocyanide catalyzed asymmetric reactions was proposed (Fig. 5a) [62][63][64] . Taking the asymmetric Kita-Spirocyclization as an example, the phenyl iodine pendants of polyisocyanide were initially oxidized to active hypervalent iodane (IA) by mCPBA.…”
Section: Mechanism Studymentioning
confidence: 99%
“…Our recent work has revealed that these types of helical polymers can act as polymer-supported catalysts for asymmetric catalysis and amplify a chiral environment. [65][66][67][68] Based on our long-term research interest in polyisocyanide chemistry and cooperative catalysis, 33,69,70 we hypothesized that optically active polyisocyanides could provide a highly tunable platform to realize asymmetric cooperative catalysis for kinetic resolution. In our molecular design of these chiral polymer-supported catalysts, the Co(III)-salen unit is decorated onto the pendant group of optically active polyisocyanides via living/control coordination polymerization of isocyanide monomers containing the salen moiety and then post-metalation of the Co(III) ion (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…92,93 Although previously published approaches using a homogenous catalyst for preparing spiro derivatives are valuable, these catalysts suffer from some disadvantages, such as high cost, drastic separation from the reaction mixture, long-duration reaction, and high temperature. 94–99 Over recent years, various heterogenized organic polymer catalysts based on helical polymers (single-handed helical polyisocyanides), 100 polyethyleneglycols (PEG-Ni NPs, PEG-OSO 3 H), 101,102 polystyrene (PS@GO-Fe 3 O 4 ), 86 chitosan (Fe 3 O 4 @CS-SO 3 H NPs, Bmim(OH)/chitosan/C 2 H 5 OH), 103,104 cellulose (cellulose-SO 3 H, nano-cellulose-SbCl 5 , Cu 2 O@MCC, NiII(BAPTE)(NO 3 ) 2 -Cell nanocatalyst), 105–108 polyaniline (PANI/Fe 3 O 4 /CNT), 109 and collagen protein (Fe 3 O 4 @SiO 2 /ECH/IG) 110 have been used in the synthesis of spiro-fused[4 H -pyran]. Although the above-mentioned catalytic systems can be readily separated, the recycling times were low (probably due to leaching or tedious workup).…”
Section: Introductionmentioning
confidence: 99%